Agent Responsibilities in Life Insurance Marketing Practices for Legal Protection for Consumers - Mochamad Arifinal (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The legislation provides legal protection to policyholders as insurance consumers. Protection of policyholders as insurance consumers is regulated in several regulations, such as the Criminal Code and the Civil Code. The Criminal Code Number 2 of 1992 concerning Business Insurance, the Criminal Code Number 8 of 1999 concerning Consumerism Protection, also regulated in the rules of the Professional Code of Agents Indonesian Life Insurance. This research aims to know whether the insurance law is sufficient to regulate the agent's responsibility to consumers in the practice of marketing life insurance and how the agents' responsibility of marketing life insurance to the protection of penalties to consumers. This research used a juridical normative method approach. This method focused on library data and was supported by field research to support existing data. The results of the research indicate that insurance, which includes the Commercial Code, the Civil Code, and Law Number 2 of 1992 concerning Business Insurance, has not been sufficiently regulated regarding the responsibilities of agents. Therefore, other regulatory agencies are needed, such as codes of ethics and professional agents (self-regulation); the establishment of draft laws or the brokering of agents into codes or laws; and consumer protection law provides legal protection to consumers through the regulation of rights and obligations to businessmen and consumers, which also regulates the responsibilities of businessmen in marketing a product, both in the form of services and goods